2018
DOI: 10.1021/acs.jctc.8b00475
|View full text |Cite
|
Sign up to set email alerts
|

Geometry Optimizations in a Subsystem Density Functional Theory Formalism: A Benchmark Study

Abstract: We present a benchmark study on equilibrium structures optimized with subsystem density functional theory (sDFT) employing a new analytical gradient implementation in the program SERENITY. Geometry optimizations are performed on all complexes of the S22 [Jurečka et al. Phys. Chem. Chem. Phys. 2006, 8, 1985–1993] and A24 [Řezáč and Hobza. J. Chem. Theory Comput. 2013, 9, 2151–2155] test sets. While some combinations of approximate exchange-correlation (XC) and nonadditive kinetic-energy functionals (e.g., L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 59 publications
(129 reference statements)
0
10
0
Order By: Relevance
“…Typically, classic density functional methods, such as the BP86 and B3LYP, were not considered as suitable methods to calculate weak interactions like halogen bonds owing to the serious underestimation of dispersion effects. ,, Empirical dispersion correction schemes were developed by Grimme and coworkers to solve this problem, among which the DFT-D3 and DFT-D4 models have shown satisfactory performance in describing a variety of weak interactions. Empirical dispersion-corrected functionals such as B97-D, BP86-D, and ωB97XD have already been successfully applied in the calculation of various XB complexes. ,,, On the other hand, Truhlar’s team developed a series of new functionals by fitting the parameters from data sets with noncovalent interactions included. Among them, functionals represented by M06-2 X showed excellent performance in various benchmark tests ,,, and could be used as the recommended methods in describing the halogen-bonding properties. Additionally, DiLabio et al suggested that the common empirical dispersion-corrected functional methods may still have room for improvement in describing halogen bonds, especially in cases that charge transfer interactions play the significant role .…”
Section: Quantum Mechanical Methodsmentioning
confidence: 99%
“…Typically, classic density functional methods, such as the BP86 and B3LYP, were not considered as suitable methods to calculate weak interactions like halogen bonds owing to the serious underestimation of dispersion effects. ,, Empirical dispersion correction schemes were developed by Grimme and coworkers to solve this problem, among which the DFT-D3 and DFT-D4 models have shown satisfactory performance in describing a variety of weak interactions. Empirical dispersion-corrected functionals such as B97-D, BP86-D, and ωB97XD have already been successfully applied in the calculation of various XB complexes. ,,, On the other hand, Truhlar’s team developed a series of new functionals by fitting the parameters from data sets with noncovalent interactions included. Among them, functionals represented by M06-2 X showed excellent performance in various benchmark tests ,,, and could be used as the recommended methods in describing the halogen-bonding properties. Additionally, DiLabio et al suggested that the common empirical dispersion-corrected functional methods may still have room for improvement in describing halogen bonds, especially in cases that charge transfer interactions play the significant role .…”
Section: Quantum Mechanical Methodsmentioning
confidence: 99%
“…It can be observed that the electronic configuration characteristics calculated at three functionals of the studied compounds are qualitatively consistent. To further confirm the effects of dispersion and the pure functional on the structural features, we also performed the calculations at the UB3LYP/6-31G(d) level, in conjunction with the D3 version of Grimme's dispersion, 27 as well as conducted optimizations on the studied compounds by using the BP86 functional, 28 and the calculated results are shown in Fig. S1 and S2 in the ESI,† respectively, both of which show a similar tendency with those results calculated at other three functionals.…”
Section: Resultsmentioning
confidence: 99%
“…Before concluding this work, it may be interesting to put forward some assessments in terms of time statistics to be used as a basis for optimizing the computation time and speed-up any uFDE-rt-TDDFT calculations. We used a water–ammonia complex as a general test-case, where the geometry of the adduct was taken from ref and water is the active subsystem.…”
Section: Resultsmentioning
confidence: 99%